(untitled) (Research, Society and Development, 2021)
The objective of this case report was to describe the retreatment of an immature upper right central incisor in a 20-year-old female patient after unsuccessful endodontic treatment, who had probable clinical-radiographic diagnosis of a large periapical inflammatory cyst and persistent fistula. After removing the root canal filling material, disinfection of the root canal system, and successive intracanal medication changes over 60 days, the fistula remained active. Therefore, parendodontic surgery was performed. The root canal system was obturated, the periapical cyst was surgically enucleated, and retro-obturation with mineral trioxide aggregate was performed. We used the guided tissue regeneration technique with a xenograft and resorbable membrane. On histopathological examination, we observed bacterial colonies present in the lumen of the cystic lesion. Clinical evaluation, periapical radiograph, and cone-beam tomography confirmed complete healing of the periapical area of the affected tooth. The treatment success was verified by periapical healing over a follow-up period of 21 months.